Unraveling Market Shifts: A Study of Abnormal Returns, Trading Activity, and Volume Dynamics Around the COVID-19 Pandemic - Mochammad Ilyas Junjunan; Adinda Angie Dwi Santoso; Binti Shofiatul Jannah; Muhammad Safdar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study (case study on LQ-45 stocks on the Indonesia Stock Exchange) will examine the differences between these times to evaluate abnormal returns, trading frequency activity, and volume activity before and after the Covid-19 pandemic. In the approach, quantitative methodology is used. A purposive sampling strategy is used to collect the data with a population of 60 enterprises from 2018 to 2021, and a sample of 28 companies is obtained. The results of the investigation showed that the abnormal returns before and after the COVID-19 epidemic did not differ significantly. However, a study on trading volume activity and trading frequency activity revealed that there were notable variations between the COVID-19 pandemic and other times. Investors will compete with one another to sell their shares as a result of their worries that the COVID-19 case may spread and become challenging to handle. Investors prefer to sell these shares rather than hold onto businesses that carry a significant chance of financial loss as a result.